Relationship between Fork Progression and Initiation of Chromosome Replication in E. coli - Guzmán, Elena C.; Salguero, Israel; Martín, Carmen Mata; Acedo, Elena López; Guarino, Estrella; Sánchez-Romero, Ma Antonia; Norris, Vic; Jiménez-Sánchez, Alfonso (IntechOpen, 2011)
None